The Impact Of Community Responses Toward Unlabeled Halal Peyek Crackers In The Wonomulyo Market Complex - Febrianti, Lisma; Ramayani, Indah; Asrandi , Asrandi (Fakultas Ekonomi & Bisnis Universitas Muslim Indonesia, 2025)
This study aims to examine public responses toward